2007
DOI: 10.1038/modpathol.3800784
|View full text |Cite
|
Sign up to set email alerts
|

Significance of C4d staining in ABO-identical/compatible liver transplantation

Abstract: Complement degradation product C4d has become an important marker of humoral or antibody-mediated rejection in renal and heart allograft biopsies. Although there have been several reports on the detection of C4d in liver allografts, the significance of C4d in liver transplantation and its relationship with humoral rejection are still not clear. We investigated the frequency and pattern of C4d staining in liver allograft biopsies with reference to preoperative lymphocyte crossmatch tests, which detect donor-rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
85
1
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 38 publications
7
85
1
1
Order By: Relevance
“…In day 7 protocol biopsy samples, we observed that diffuse C4d deposition in all compartments of the liver was seen only in recipients with concomitant circulating DSAs, regardless of the preoperative cross-match status. 24 In LDLT, diffuse perivenular, sinusoidal, lobular, and stromal C4d staining was more often observed in cross-match-positive recipients, 42 although this does not seem to correlate with the incidence of acute rejection or CR. 25 Among pediatric LDLT recipients with protocol biopsy samples obtained at least 10 years after the operation, no significant difference in C4d deposition was observed between the recipients with circulating DSAs and the recipients without circulating DSAs.…”
Section: Histological Findings In Liver Transplant Recipients With Domentioning
confidence: 99%
See 2 more Smart Citations
“…In day 7 protocol biopsy samples, we observed that diffuse C4d deposition in all compartments of the liver was seen only in recipients with concomitant circulating DSAs, regardless of the preoperative cross-match status. 24 In LDLT, diffuse perivenular, sinusoidal, lobular, and stromal C4d staining was more often observed in cross-match-positive recipients, 42 although this does not seem to correlate with the incidence of acute rejection or CR. 25 Among pediatric LDLT recipients with protocol biopsy samples obtained at least 10 years after the operation, no significant difference in C4d deposition was observed between the recipients with circulating DSAs and the recipients without circulating DSAs.…”
Section: Histological Findings In Liver Transplant Recipients With Domentioning
confidence: 99%
“…For example, the staining of hepatocytes with C4d antibodies is observed as a result of ischemia/reperfusion injury, 41 and it is not an antibody-mediated injury marker. Diffuse portal C4d staining can be seen in up to two-thirds of biopsy samples with ACR, 21,42 although a recent report demonstrated that there is no difference between cases of ACR with or without diffuse C4d deposition with respect to the Banff grade of rejection or liver enzymes. 23 Several studies have looked at the differences in the location of C4d deposition between DSA-positive and DSA-negative liver transplant recipients.…”
Section: Histological Findings In Liver Transplant Recipients With Domentioning
confidence: 99%
See 1 more Smart Citation
“…It is absolutely necessary to compare biopsy samples of dysfunctional tissue with normal control livers and allografts with different diagnoses. Many studies have reported a high rate of C4d positivity in various locations of the liver and with various diagnoses (see Table 2 in Sakashita et al 7 as well as Bellamy et al 8 and Hori et al 9 ). Hori et al reported that 23 of 27 ABO-incompatible living donor liver transplants showed C4d positivity in the portal endothelium, and they did not mention sinusoidal staining.…”
Section: To the Editorsmentioning
confidence: 99%
“…Focal deposition of C4d in liver is found in a variety of conditions and is generally regarded as of little clinical impact. There are reports that show extensive C4d deposition is associated with AMR and correlated with graft survival (10). However, C4d deposition in liver has been reported in several other conditions, such as acute cellular rejection, chronic rejection, recurrent diseases including auto- Fig.…”
Section: The Significance Of C4d Immunostaining In Livermentioning
confidence: 99%